Formal ontologies and their role in the integration of library resources - Szulc, Jolanta (Qualitative and Quantitative Methods in Libraries, 2017)
The purpose of this article is to analyze and compare the resources including knowledge organization systems used in the Polish scientific libraries. The study was based on analysis of the systems available in the libraries of some universities in Poland and other scientific libraries. This paper presents the vocabulary control systems used in Polish academic libraries: subject heading language (KABA and MeSH), thesauri, classification and formal languages used to write these structures. In conclusion, the paper presents proposals for future research. The results of the study are addressed primarily to the specialists in the library and information science, librarians and professionals involved in the creation of the domain and developing a formal ontology.